Mengungkap Pengaruh Dana Pihak Ketiga dan Modal Sendiri terhadap Pembiayaan BPRS: Analisis Moderasi Inflasi - Fauziyah, Auliya; Syahbudi, Muhammad; Inayah, Nurul (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Islamic financial institutions in Indonesia have experienced tremendous expansion. Sharia-compliant banks play a crucial role in collecting public funds and channeling financing to strengthen the economy. The purpose of this research is to examine the influence of Third-Party Funds (DPK) and Equity Capital on financing at BPRS Puduarta Insani, and to analyze the moderating role of inflation in these relationships. Using secondary data from the Financial Services Authority (OJK) for the period 2015-2023, this study applies Moderated Regression Analysis (MRA). The findings indicate that Third-Party Funds (DPK) have a significant positive effect on financing (β = 0.751; p < 0.05), confirming their role as a primary source of intermediary funds, while Equity Capital was not found to have a significant effect. The study's key finding is the significant role of inflation as a moderating variable. Inflation was proven to weaken the influence of DPK on financing (interaction coefficient = -0.322; p < 0.05) as well as the influence of Equity Capital (interaction coefficient = -0.204; p < 0.05). This model explains 89.4% of the variance in financing (R² = 0.894). This implies that in high-inflation situations, the role of DPK and capital in supporting financing expansion tends to decline due to greater risk considerations by the bank.